História dos militares na cidade de Crato: tropas, milícias e ordenanças (1718-1870) - Silva, Maria Icleide Viana da (2015)
In this study of the historical trajectory of "military" in the city of Crato compared with the performance of "military" is the capital of Pernambuco militia troops, and ordinances or in the National Guard during the period from 1718 until the late 1870s that context in several national military systems, and regional were consolidated with the Patent and Registration of Patents during that troops Cariri and the city of Crato. Through dialogue with the historiography related to the topic, we sought to understand the functioning and the influence of the military Pernambucans revolutionary movements in the city of Crato in the Northeast region, and how did this organization of the military hierarchy, and analyze the effective participation of church in state affairs. We found some political, economic and social events that motivated the participation of family Alencar in the revolutions of 1817-1824 and thus present the "Organic Act of 1817," the Republic and the arrests of "alencares" in Bahia. It concludes with the role of the military in the period 1851 and 1900, and the recruitment of troops and military and police organization of Crato in 1870 The research presented here, stopped in documentary sources produced in the Royal Letters, state file Ceará, regional literature, local, were used for the study of the two realities. Research has shown that the military was directly responsible for the implementation of the civilizing process of the city, thereby confirming the influences they have had on military and civil society of the city of Crato.